Monotonic Limit Properties for Solutions of BSDEs with Continuous Coefficients - ShengJun Fan; Xing Song; Ming Ma (International Journal of Mathematics and Mathematical Sciences)
This paper investigates the monotonic limit properties for the minimal and maximal solutions of certain one-dimensional backward stochastic differential equations with continuous coefficients.